Strengthening Soil Health Systems in West Africa: 2025 Progress of the Regional Hub for Fertilizer and Soil Health (RHFSH) Establishment - Kadja, Lionel Axel; Oladipupo, Ilerioluwa Deborah; Dalaa, Mustapha Alasan; Ampadu-Boakye, T. (2025)
This 2025 update provides an overview of IITA’s coordinated efforts toward establishing and operationalizing the Regional Hub for Fertilizer and Soil Health (RHFSH), in alignment with AICCRA Performance Indicator (IPI) 1.2. The report presents key milestones achieved in the reporting period, focusing on developing governance structures, stakeholder engagement processes, country-level collaborations, and progress in deploying the Hub’s core functions. Collectively, these achievements demonstrate significant advancement in promoting sustainable soil health and fertilizer management systems across West Africa